(untitled) (Experimental biology, 2018)
The results of development cycle of Pseudoperonospora cubensis Rostowz and biometric index of Kazakhstani population of fungi are presented in this article. In result of study of morphological and biological characteristics, fungi oospores are detected on the affected cucumber leaves. Oospores were grown up in zoosporangium with zoospores, greyish-violet incrustation was formed on the lower side of leaf which consist from conidia carriers and conidia. Conidia were frown up in zoospores and zoosporangia, in the following oospores were formed in the result of fusion oogonia with antheridia. Biometrical indexes were shown that samples from Zhambylskoi oblast by the size is less than samples from more humidified places of Almaty oblast. Conidiophores from the Kordai region samples along the length and width were formed 148.0-499.5x4.3-7.5 nm, and from the Enbekshikazakh region samples the conidiophores were rather large in length and width, 150.0-490.0x6.3-8.6 nm. For temperature conditions had been shown that the most favorable temperatures for conidia germination were 16-18 °С and 20-22 °С. At these temperatures a great studied fungi conidia in 1.5-2 hours was formed germ tubes.